Akachi Adimora-Ezeigbo's snail-sense feminism: a subtle womanist agenda For Nigerian children's and adults' literature - Olatunji, Rotimi Anne (2020)
This thesis examines how the Nigerian woman writer, Akachi Adimora-Ezeigbo’s snail-sense feminism manifests in some selected literary works by the writer. The thesis makes use of a selection of her works for adults, young adults and children and foregrounds the details of her snail-sense in the works. Acknowledging the importance of tradition of storytelling in situating cultural gender experiences within the Nigerian social and cultural world, the thesis addresses the cultural location of Adimora-Ezeigbo’s stories as the propelling force behind the employment of her snail-sense feminist strategy. In this way the thesis can be seen to respond to Adimora-Ezeigbo’s literary oeuvre as an acknowledgement and a continuation of the different feminist models that came before hers and have been developed by Nigerian women writers. The thesis examines the gender nuances of Adimora-Ezeigbo’s children’s literature as subtle gestures towards creating early gender awareness which runs in line with her gender complementarity within the snail-sense feminist strategy. Even though the research eventually found that despite the writer’s claim to changing the portrayal of girl-child characters in literature meant for children, her fairytales for children still largely follows established patterns. Through the sample texts used in the research, the thesis establishes that Adimora-Ezeigbo’s snail-sense model is a variant which still follows the same path with earlier models by Nigerian women writers. The thesis demonstrates that Adimora-Ezeigbo’s literary oeuvre contributes to the Nigerian womanist literary debates especially in terms of the focused attention she gives to furthering the trajectory of a new feminist alternative. While a chapter each is devoted to examining the deployment of snail-sense in Adimora-Ezeigbo’s adult and young adult fiction, the thesis devotes two chapters to the examination of the snail-sense feminist strategy in her children’s literature because this is the area where she has written the most and an area where a dearth of feminist engagement still exists in Nigeria. While a chapter explores the development of women’s writings in Nigeria since independence, a chapter examines how Adimora-Ezeigbo’s trilogy for adults engages in a womanist exploration of women’s history of power over time in Nigeria using the snail-sense feminist strategy. The two chapters on children’s literature examine how her children’s books engage with both retelling of oral tales and framing contemporary social issues in ways which consider the welfare of children within the snail-sense purview. The thesis also examines the ways she reworks old fairy tales to suit womanist purposes even though these do not show in the strong and serious ways she does this in the adult literature. The chapter on the young adult literature examines a text which shows Adimora-Ezeigbo’s comment on the engaging and burning issue of women trafficking as a bane to women‘s development but a situation which calls to the importance of the snail-sense strategy in reworking a path of emancipation for trafficked women.